PENGARUH KOMPETENSI DAN KOMITMEN OGANISASIONAL TERHADAP KINERJA KARYAWAN PADA PT BANK PAPUA CABANG WAMENA - KENELAK, DINUS; AREROS, WILLIAM; RUMAWAS, WEHELMINA RUMAWAS (JURNAL ADMINISTRASI PUBLIK, 2019)
This study aims to determine the effect of (1) competence on employee performance at PT Bank PapuaBranch Wamena, (2) organizational commitment to employee performance at PT Bank Branch Wamenaand (3) competence and organizational commitment to employee performance at PT Bank Papua BranchWamena . This research is a quantitative research using questionnaire assistance as an instrument ofresearch. The population used in this study is PT Bank Papua Branch Wamena, and the sample is anemployee of PT Bank Papua Branch Wamena. 39 respondents were taken using the Slovin formula andwill use the purposive sampling method in distributing questionnaires. This study will use multiple linearregression analysis with the help of MSS. The results of the study show that the 3 hypotheses in this studywere accepted.Keywords: Competence, Organizational Commitment and Employee Performance